Analysis of the influence of living environment and age on vaginal fungal microbiome in giant pandas (Ailuropoda melanoleuca) by high throughput sequencing. (February 2018) - Chen, Danyu; Li, Caiwu; Feng, Lan; Zhang, Zhizhong; Zhang, Heming; Cheng, Guangyang; Li, Desheng; Zhang, Guiquan; Wang, Hongning; Chen, Yanxi; Feng, Mingfu; Wang, Chengdong; et al.
Abstract: A recent study has described the normal vaginal bacterial community in giant pandas, but there is a lack of knowledge of the fungal community residing in the vagina of giant pandas. In order to comprehensively understand the vaginal fungal microbial diversity and abundance in giant pandas, high throughput sequencing was used to analyse the ITS1 region, based on thirteen samples taken from the pandas' vaginas, which were grouped by sampling points and age. The results showed that the most abundant phyla were Basidiomycota (73.37%), followed by Ascomycota (20.04%), Zygomycota (5.23%), Glomeromycota (0.014%) and Chytridiomycota (0.006%). At the genus level, Guehomyces (37.92%) was the most abundant, followed by Cladosporium (9.072%), Trichosporon (6.2%) and Mucor (4.97%). Furthermore, Candida only accounted for a low percentage of the vaginal fungal community. With the saturation of rarefaction curves and fungal diversity indices, the samples from Dujiangyan and Chungking Safari Park (DC group) showed a higher fungal species richness and diversity than other living environments. Shannon diversity indices showed significant difference between group WL (Wolong nature reserve) and DC ( P < .05). Additionally, a higher diversity was found in ten to fifteen years old (Group 2) than other groups. Group 2 and Group 3 displayed significant differences in the diversities of their vaginal fungal communities ( P < .05). These data that has been collected from this research will be helpful for further study to improve the reproductive status of giant pandas. Highlights: This is the first time to use high throughput sequencing to analyze the vaginal fungal microbiome of giant pandas. We can intuitively know the dominant fungal flora in thirteen vaginal samples of giant pandas. Shannon diversity indices showed significant difference between group WL and DC( P < .05), Group 2 and Group 3 ( P < .05). We discussed that whether high fungal community richness and diversity related to the reproductive status of giant pandas.